The Effects of Emotional and Spiritual Intelligence on Self-Control - Fadlilah, Ainun; Sutoyo, Anwar; Murtadho, Ali (Jurnal Bimbingan Konseling, 2022)
Both emotional and spiritual intelligence help individuals do self-control. This study aimed at proving the extent to which emotional and spiritual intelligence affect students’ self-control. This correlational study involved 329 students from 4 islamic junior high schools in Semarang City selected using a cluster sampling technique. Their data were analyzed using a hierarchical regression analysis. Findings have proved that both spiritual and emotional intelligence had significant effects on self-control. It can be implied that students need to be assisted in performing self-control for to achieve future success by reinforcing emotional and spiritual intelligence.